(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
Globalization, as a phenomenon and concept, raises a number of complex matters, issues but also controversies, thus the opinions regarding globalization are divided. There are opinions that sustain that a major impact of globalization on Christian churches exists and will be felt in the theological and in the idealistic field. The core problem that arises, however, related to the phenomenon of globalization, in terms of religion, is related to the manner in which religion can survive, keeping its independence, in a framework that wants to be globalized and that exerts serious pressure towards the relativization of all claims of truth ownership.